Effect of Lumbar Epidural Steroid Injections on Osteoporotic Fracture and Bone Mineral Density in Elderly Women with Diabetes Mellitus - Minsoo Kim; Jiwon Bak; Sejin Kim; Hee-Jeong Son; Seong-Sik Kang; Jin Hue; Byeongmun Hwang; Seung Koo Lee (Pain Research and Management)
The incidence of osteoporosis and diabetes mellitus (DM) is known to increase with aging. DM is associated with osteoporotic fractures and decreased bone mineral metabolism. However, no studies have compared the effects of DM on the changes in bone mineral density (BMD) and osteoporotic fracture after epidural steroid injections (ESIs). The present study aimed to analyze the relationship between ESI and BMD changes in elderly women with and without DM. The medical records of elderly women who underwent ESI were retrospectively analyzed. All patients had radiographic and BMD assessments performed before and after receiving lumbar ESIs. A total of 172 patients were divided into two groups according to the presence of DM. The duration of BMD monitoring was 16.1 and 16.8 months in the non-DM and DM groups, respectively. The mean total number of ESIs was 3.4 and 3.2, and the mean cumulative administered dose of glucocorticoids (dexamethasone) was 17 and 16 mg in the non-DM and DM groups, respectively. There were no significant differences between baseline and posttreatment BMD in the lumbar spine, total femur, and femoral neck region in either group. The incidence of osteoporotic fractures at the hip joint and thoracolumbar spine was not significantly different in both groups. ESIs could be used without concerns regarding osteoporosis and fractures in elderly women with DM if low doses of glucocorticoids are used.